Multi Light Sources Enhancement using Double PANDA Ring Resonators - S. Songmuang; S. Punthawanunt; S. Mitatha; P.P. Yupapin (My University, 2011)
Abstract We propose the interesting results of light pulse propagation within a double PANDA ring resonator system. We use the technique of Finite Difference Time Domain (FDTD) which is implemented by the scientific programming method known as OPTI-WAVE PROGRAMMING to simulate and analyze the dynamic wave forms of propagating light pulse within the desired system. By using the input Gaussian pulse with center wavelength at 1,300 nm and the other practical parameters into the system, results obtained have shown that the multi wavelength light sources can be generated and achieved, and the dynamic behaviors of pulses propagation within the system can be seen.
Keywords: Split-ring resonator; Photonic and Optical Devices